A modelling approach to prepare synthetic urine for struvite precipitation studies - Soltani, Saeede (Water science and technology : a journal of the International Association on Water Pollution Research, 2023)
Nutrient recovery from wastewater is an effective strategy to prevent eutrophication and provide value for the treatment process. Human urine is a small but highly nutrient-rich stream in the total flux of domestic wastewater from which struvite (MgNH4PO4.6H2O) could be recovered and used as a fertiliser. Consequently, synthetic urine was used in most struvite precipitation studies, due to biohazard issues in real human urine. A modelling approach was developed to formulate synthetic urine recipes based on elemental urine composition, using matrix solving strategy to select and quantify chemical salts for synthetic urine preparation. The model also included mass balance, chemical speciation, and equilibrium dissociation expression for solution thermodynamics predictions in the formulated urine. In this study, synthetic solutions of fresh and stored urine were assessed with this model using Engineering Equation Solver (EES) software to calculate the quantity of salts, pH, ionic strength, and struvite saturation index. Simulation results in EES were successfully verified using PHREEQC simulations, while model validation comprised the examination of urine composition with their reported recipes